PERAN TEKNOLOGI DIGITAL DALAM MENINGKATKAN STRATEGI BELAJAR PADA REMAJA AWAL DAN AKHIR - ariyanti, suci (STIT Darul Hijrah Martapura, 2025)
AbstractThe role of digital technology in improving learning strategies of early adolescents (12–15 years old) and late adolescents (16–18 years old) is the subject of this study. Data were analyzed descriptively qualitatively into three main themes: the contribution of technology to the learning process, challenges with digital distractions and literacy, and solutions to optimize the use of technology. This literature review includes national journals published from 2019 to 2024. The results show that early adolescents prefer visual-interactive learning, such as YouTube Edu and Kahoot! While late adolescents prefer independent learning using e-books, Google Classroom, Scholar, and other online course platforms. Gamification, integrated information systems, regular teacher training, and blended learning have been shown to improve student learning and achievement. However, the active role of teachers and parents in mentoring is very important because social media distractions and limited digital literacy are still major problems.Keyword: digital technology; learning strategies; digital literacyAbstrakPeran teknologi digital dalam meningkatkan strategi belajar remaja awal (12–15 tahun) dan remaja akhir (16–18 tahun) adalah subjek penelitian ini. Data dianalisis secara deskriptif kualitatif ke dalam tiga tema utama: kontribusi teknologi dalam proses belajar, tantangan dengan distraksi digital, dan solusi untuk optimalisasi penggunaan teknologi. Kajian pustaka ini mencakup jurnal nasional yang diterbitkan dari 2019 hingga 2024. Hasilnya menunjukkan bahwa remaja awal lebih suka pembelajaran visual-interaktif, seperti YouTube Edu dan Kahoot. Sementara remaja akhir lebih suka belajar mandiri dengan menggunakan e-book, Google Classroom, Scholar, dan platform kursus online lainnya. Gamifikasi, sistem informasi terintegrasi, pelatihan guru rutin, dan blended learning telah terbukti meningkatkan pembelajaran dan prestasi siswa. Namun, peran aktif guru dan orang tua dalam pendampingan sangat penting karena distraksi media sosial dan keterbatasan literasi digital masih menjadi masalah utama.